MANAGERIAL STRATEGIES IN TEACHER WELFARE POLICIES FOR ISLAMIC EDUCATION: A COMPARATIVE STUDY OF INDONESIA AND MALAYSIA - Sisfi Khafidz Fanani (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
Teacher welfare in Islamic education has become a strategic issue in Indonesia and Malaysia because it is directly related to professionalism, instructional quality, and the sustainability of Islamic educational institutions amid bureaucratic pressures and limited resources. Although both countries have established formal policies on teacher welfare, their practical implementation often fails to align with normative policy objectives. This article aims to analyze how the managerial strategies of school principals and madrasah leaders mediate the implementation of teacher welfare policies within the institutional contexts of Indonesia and Malaysia. This study employs a qualitative descriptive approach based on a literature review of scholarly articles, research reports, and relevant policy documents. The analysis is conducted through a synthesis of the literature using Van Meter and Van Horn’s Policy Implementation Theory, Herzberg’s Two-Factor Theory, and the concept of Islamic Work Ethic. The findings indicate that teacher welfare is not determined solely by policy design, but largely by managerial strategies such as budget prioritization, workload management, communication, and teacher participation. The results also show that the fulfillment of hygiene factors and the strengthening of motivators, when framed by Islamic values of trust (amanah), justice, and responsibility, enhance teacher satisfaction and performance. This study underscores the importance of value-based and context-sensitive school leadership. Future research is recommended to incorporate field-based data in order to provide a richer and more contextualized understanding.